Predictors of First-Pass Effect in Endovascular Thrombectomy With Stent-Retriever Devices for Acute Large Vessel Occlusion Stroke - Chen, Chu; Zhang, Tangqin; Xu, Youqing; Xu, Xiangjun; Xu, Junfeng; Yang, Ke; Yuan, Lili; Yang, Qian; Huang, Xianjun; Zhou, Zhiming (Frontiers in Neurology, 2022)
Background and purpose Successful recanalization after first-pass of the device in endovascular thrombectomy (EVT) can significantly improve patients’ prognosis. We aimed to investigate the possible factors that influence on achieving modified first-pass effect (mFPE). Methods We retrospectively analyzed the patients underwent EVT caused by anterior circulation large vessel occlusion stroke (ALVOS) in our center. The mFPE was defined as a successful recanalization (modified Thrombolysis in Cerebral Infarction (mTICI) 2b/3) after one pass of the device without rescue therapy. The baseline characteristics, procedural and clinical outcomes were collected. Univariate and multivariate regression analysis was used to explore the predictors of mFPE and the relationship between mFPE and prognosis. Results There were 278 patients (age, 69.3±10.9 years, male, 51.1%) included, 30.2%(n=84) of them achieved mFPE. We found the higher clot burden score (CBS) (OR=1.384; 95%CI:1.119-1.713; P=0.003), the truncal-type occlusion (OR=0.354; 95%CI:0.179-0.701; P=0.003) and the favorable anatomy of both extracranial segment (OR=0.506; 95%CI: 0.288-0.889; P=0.018) and intracranial segment of internal carotid artery (ICA) (Type IV vs. Type I: OR:0.195, 95%CI:0.041-0.918, P=0.039) were associated with achieving mFPE. Moreover, mFPE were significantly associated with improved clinical outcomes (OR:0.347; 95%CI:0.159-0.760; P=0.008). Conclusions The CBS, tortuosity of ICA and angiographic occlusion type were independent predictors of achieving mFPE. The rate of improved clinical and safety outcome was higher in patients with mFPE, which has important clinical significance.